A comparative analysis of the implications of the Islamic religion on corporate capital structures of firms in emerging market countries. Issue 3 (12th August 2014) - Gunn, Theresa; Shackman, Joshua
Abstract : Purpose: – The purpose of this study is to examine the impact of the Muslim religion on firm capital structure. Design/methodology/approach: – The authors compare financing patterns in Muslim versus non-Muslim countries using 658 firms in 16 countries covering a period of seven years. Findings: – No significant differences between Muslim and non-Muslim countries were found in terms of total debt ratios. However, significant differences were found in the choice of short-term versus long-term debt, with firms in Muslim countries showing a strong preference for short-term debt. Research limitations/implications: – The findings confirm existing theories on the impact of the Islamic religion on short-term versus long-term debt preferences. However, the findings concerning the lack of an impact of the Islamic religion on total debt preferences are surprising and contrary to existing theories. Practical implications: – Firms in Muslim countries appear to have the flexibility to adopt overall leverage ratios comparable to those in non-Muslim countries. However, firms in Muslim countries may be disadvantaged in that there appear to be impediments to the use of long-term debt. Originality/value: – This paper presents one of the first empirical studies of the impact of the Muslim religion on corporate financing choices across a large cross-section of firms in Muslim and non-Muslim countries.